Combustion characteristics of palm shells and palm fibers using an inclined grate combustor / Wan Ahmad Najmi Wan Mohamed and Nik Rosli Abdullah (Faculty of Mechanical Engineering and University Publication Centre (UPENA), 2008)
Biomass fuel can be an alternative fuel for industries that produces a lot of agriculture waste (like FELDA), which can convert the fuel to useful heat energy. Numerous research works have been carried out to study the combustion characteristics of agricultural solid wastes, however, every result is unique due to differences in the process and hardware. This paper publishes results based on the combustion experiments of palm kernel shell and palm fiber using an under-fire inclined grate combustor developed locally. This work aims to generate combustion data for future research development of the palm oil wastes as an alternative fuel. The analysis is based on theoretical and experimental energy outputs, emission analysis and combustion behavior. In general, palm shells have a calorific value of 16.9 MJ/kg, while palm fibers reported calorific value is 9.2 MJ/kg. Actual energy released during the combustion process was determined from the flue gas compositions using thermodynamics analysis of combustion reactions. The combustion chamber design limits the actual energy conversion at a range of 24% to 32%, where the maximum flue gas energy was determined at about 5.4 MJ/kg for palm shells and 2.5 MJ/kg for palm fiber. Critical factors identified in enhancing the combustion performance are the air supply, air-fuel mixing and fuel distribution.